ISOLATION AND DETECTION OF ANTIMICROBIAL SUSCEPTIBILITY PATTERN AND ESBL PRODUCTION OF ESCHERICHIA COLI IN CHILDREN WITH GASTROENTERITIS - K.SENTHILKUMARAN (International Journal of Pharma and Bio Sciences, 2012)
Diarrhoeagenic E.coli is the most common bacterial pathogen causing childhood diarrhoea. In this study 100 stool samples from children having diarrhoea and 25 samples from healthy children were collected and 39 and 7 E.coli was isolated respectively. The strains were screened for ESBL production. 28 isolate (71.8%) in double disc synergy method and 22 isolate (56.4%) in phenotypic confirmation method showed ESBL production. In phenotypic method by using PCR, 24 (61.5%) isolate showed CTX-M gene and 3 (7.7%) isolate showed SHV gene. This study showed high prevalence of ESBL in E.coli strains which warrants effective screening technique in routine laboratories and usage of combination treatment regimen with Clavulanic acid to overcome the treatment failure.